Note: The Impact of Leadtime and Years of Competitive Rivalry on Pioneer Market Share Advantages - Huff, Lenard C.; Robinson, William T. (Management Science, 1994)
Research has established that for surviving brands, market pioneers have a higher average market share than later entrants. By moving first, market pioneers often develop sustainable market share advantages. Longer leadtime, which is the time between entries, should increase these pioneer advantages. Using two leadtime measures, this prediction is supported across 34 categories of frequently purchased consumer goods. Increasing the years of competitive rivalry should help a later entrant slowly reduct the pioneer's market share advantage. After more than two decades in the market, second entants have eliminated the pioneer's market share advantage, but third and later entrants continue to trail the pioneer.